Dampak Harga Minyak Dunia Terhadap Jumlah Uang Beredar di Indonesia Tahun 2005.Q1-2016.Q4 - Mita Pradnya Wardani; Regina Niken W.; Agus Lutfi (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
Policies taken by the government and the central bank greatly determine the size of the money supply. World oil prices play a role in increasing the money supply through inflation. The purpose of this study is to find out the most effective policy in controlling the money supply by the public, using the Vector Autoregressive (VAR) model to estimate the variables in the study. The estimation of the impulse response function and also the variance decomposition which describes how and how much influence the shock from the amount of money supply. The VAR estimation shows that the money supply is most significantly influenced by the money supply itself, economic growth, deposit rates and exchange rates while inflation does not have a significant effect on the money supply. Impulse response analysis shows that the money supply gets the fastest and most powerful response to inflation. Whereas in the description of variance decomposition, the variation explained by the large money supply affects the change in the money supply itself and the second rank is economic growth. Keywords: Oil Prices, Inflation, Gross Domestic Product, Interest Rate, Exchange Rate.